Analisis Grade Specialty Arabika Pagur Madina Menggunakan Metode AHP - Erin Alawiyah Siregar; Rama Dani Eka Putra (Journal of Engineering Science and Technology Management, 2022)
This study was conducted to identify internal and external factors that affect the quality of Pagur arabica for the export market. Furthermore, from the identification, a development strategy for export quality Arabica will be drawn up. Data were obtained from 3 specialties Arabica coffee producers. The data analysis used AHP to determine quality criteria that are in accordance with export coffee quality standards, including moisture content, value of bean defects, levels of impurities and uniform coffee bean size. A total of 10 experts were asked to choose alternatives based on predetermined criteria. The analysis of the weighting of the producer selection data in this study was carried out using the analytical hierarchy process method. The results showed that the criteria that most influenced the selection of Pagur Madina specialty arabica coffee producer grades were the criteria for bean defects with a weight of 0.409, the criteria for bean size with a weight of 0.213, the criteria for dirt content with a weight of 0.213 and the last criterion was the criterion of water content with a weight of 0.069. Meanwhile, the best producer chosen by the respondents is Producer Z with a weight of 0.678 then producer Y with a weight of 0.170 and the last producer priority is supplier X with a weight of 0.152.